A Note on the Built-in Flexibility of the Individual Income Tax - Smith, Paul E. (Econometrica, 1963)
IF ONE IS compelled to seek a substitute for the automatic stabilizing properties of flexible prices as embodied in the quantity theory equation or the real-balances effect of Pigou, it is natural to look for relief in the direction of those built-in stabilizers associated with certain government activities. It is generally recognized that the behavior of many types of government transfers and taxes tend to dampen the movements of certain key economic variables. Although they are partially hidden in the model which follows, unemployment benefits, agricultural support payments, the guaranteed annual wage, and taxes, other than the federal personal income tax, are not explicitly considered in this study. In this article we attempt to answer the following three questions: 1. In what ways are recent measurements of the efficacy of the personal income tax as an automatic stabilizer inadequate? 2. What are the statistical relationships between personal income tax receipts and other endogenous and predetermined economic variables in a jointly determined model of income determination? 3. By what proportion have the changes in the gross national product of the United States since World War II been reduced as a result of the built-in flexibility contributed by the personal income tax?